Abalakeus Southcott, 1994 is a junior synonym of “plume-footed” Eatoniana Cambridge, 1898 (Trombidiformes, Erythraeidae)—evidence from experimental rearing - Mąkol, Joanna; Sevsay, Sevgi (Zootaxa, 2015)
Eatoniana Cambridge, 1898 was previously known exclusively from active postlarval forms. In the course of experimental rearing, larvae showing a strong affinity to members of Abalakeus jahromiensis Sedghi, Saboori et Hakimitabar, 2010, were obtained from a field-collected female of Eatoniana plumipes (L. Koch, 1856). Studies of all members of Abalakeus compared with newly obtained larvae of Eatoniana, resulted in synonymisation of Abalakeus Southcott, 1994 with Eatoniana and of A. jahromiensis with E. plumipes. Complementary data to the previous diagnosis of Eatoniana and information on the biology of E. plumipes are provided. A female of E. plumipes was selected as the neotype. A key to Eatoniana spp. known from larvae is provided.